(untitled) - Passer, Michael W. (New York, 2004)
This textbook reflects its authors' experiences both as faculty members who have taught the introductory psychology course several dozen times, and, earlier, as students whose own interest in psychology was sparked by instructors who brought the introductory course to life. The text's flexible organizing framework ("Levels of Analysis"), depth of research, emphasis on critical thinking, and engaging writing help instructors convey the expanse and excitement of the field of psychology, while maintaining scientific rigor. The new third edition features a separate chapter on intelligence, chapter reorganizations, and updated research throughout.
Keywords: Psychology; Textbooks